Student motivation during open distance learning and its impacts on students’ academic performance in UiTM Seremban 3 / Aida Ariza Abdul Wahib and Madihah Zahidah Mohammad Zaidi - Abdul Wahib, Aida Ariza; Mohammad Zaidi, Madihah Zahidah (2022)
The purpose of the study to measure the students’ academic performance depends on student’s motivation during online distance learning (ODL). Students’ academic performance are very crucial and important for every students and university. Academic performance is the evaluation of a student's ability in a range of academic areas. The students might have a problems during the Online Distance Learning (ODL) at home because of unconducive environment. Students need a conducive environments and supports during the study. Normally students need to attend face to face class that have fast internet access, the finest facilities and a conducive environment. The covid-19 Pandemic has changed the way of learning and the environment of learning for students. With pandemic that resulted to this health crisis, the study on students’ academic performances is critical to reflect on the part of student’s motivation to continue the study. This research study observes the students’ ODL experience, students’ academic performance, and impacts of students’ ODL experience. A quantitative analysis of 100 students at UiTM Seremban 3 was used to perform this study, and the results indicate that there is a strong connection between students' experience in ODL and students’ academic performance. Since the study is limited to using an online survey to evaluate trust, the results are quite inflexible, and the study taken is unable to reflect the respondent' feelings and thoughts. Since the study undertaken had limitations, additional research and on this topic is desperately required. As a result, it is proposed that future research use interviews with respondents to obtain feelings, resulting in better clarity of student cooperation.